The Influence Of Brand Image On Customer Satisfaction And Customer Loyalty (Study In Padang Restaurant “Murah”) - Fitria Ariyani; M Yusuf Kurniawan (Trunojoyo University of Madura, 2022)
This study aims to examine the effect of brand image on customer loyalty through customer satisfaction. This study used quantitative methods and the technique used in sampling was non-probability sampling, accidental sampling. The data collection method uses a questionnaire with a Likert model scale that measures the independent variable (brand image), the dependent variable (customer loyalty), and the intervening variable (customer satisfaction). The sample used was 120 respondents, where the respondents were people who had visited the Padang Restaurant “Murah” in Malang City. The analysis tool used is path analysis using smartPLS. Based on the results of this study indicate that brand image has a significant direct effect on customer loyalty, besides that there is an indirect effect between brand image on customer loyalty through customer satisfaction. In the Sobel test, the results showed that brand image has a significant effect on customer loyalty through customer satisfaction. The implication of this research is that Padang Restaurants “Murah” must remain active in improving service quality and product quality in an effort to provide a consistent good impression for a good brand image so that customers can be satisfied which with this satisfaction will make customers loyal.